Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-69734
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigations of Steady and Unsteady Characteristics of a Counter Rotating Fan Model With Thickened Blades of Working Wheel

Abstract: Under VITAL Project funded by the European Community, Snecma as a project leader developed a counter rotating low-speed fan concept for a high bypass ratio engine [1–4]. At first, a counter rotating fan model (hereinafter referred to as CRTF1) with solid titanium blades was designed, manufactured and tested in CIAM’s C-3A anechoic chamber. The CRTF1 fan model had blades with a conventional thickness distribution in order to provide optimal mechanical properties and weight characteristics [1, 2].… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…No changes were reported in the total pressure ratio at the same rotational speed for uniform and nonuniform flow at the inlet but an increase in the total pressure rise and adiabatic efficiency was observed when operating under a nonuniform inflow. After that, Mileshin et al 21 found that the capacity of antidistortion of contra-rotating fan is excellent than that of the traditional rotor/stator compressor. Recently, Mistry and Pradeep 22 conducted a systemic experimental study on the low-speed contra-rotating fan.…”
Section: Introductionmentioning
confidence: 99%
“…No changes were reported in the total pressure ratio at the same rotational speed for uniform and nonuniform flow at the inlet but an increase in the total pressure rise and adiabatic efficiency was observed when operating under a nonuniform inflow. After that, Mileshin et al 21 found that the capacity of antidistortion of contra-rotating fan is excellent than that of the traditional rotor/stator compressor. Recently, Mistry and Pradeep 22 conducted a systemic experimental study on the low-speed contra-rotating fan.…”
Section: Introductionmentioning
confidence: 99%